Η συμμετοχή Τούρκων πολεμιστών στον αββασιδικό στρατό κατά τις αραβο-βυζαντινές συγκρούσεις: Οι επιχειρήσεις του στρατιωτικού αρχηγού Bughā al-Kabīr - ΤΑΚΙΡΤΑΚΟΓΛΟΥ, Κωνσταντίνος (Byzantina Symmeikta, 2018)
Αim of this study is to examine why the presence of select Turkic warriors in the Abbasid armies had little impact on the course of the Arab-Byzantine conflicts. The article focuses mainly on the campaigns conducted by the commander Bughā al-Kabīr against the Byzantine Empire and other Caliphate enemies. The small number of the Turkic warriors, as well as the difficulties encountered by the horse archers in mountainous terrains are the main reasons that there were no changes to the balance of power in the frontier conflicts.